Genomic risk profiling in advanced maternal age: a Tamil Nadu prenatal study - Sujithra Appavu; Aruni Wilson Santhosh Kumar; Mukinkumar Sonai; Vinoth Appavu (Frontiers in Medicine, 2026)
Background Advanced maternal age (AMA; > = 35 years) is associated with increased fetal chromosomal risk and is an important indication for invasive prenatal diagnosis. This study evaluates karyotyping and chromosomal microarray analysis (CMA) findings among AMA pregnancies in Tamil Nadu, India. Methods In this prospective observational study, 2,200 pregnant women aged ≥35 years who underwent amniocentesis between July 2020 and June 2021 were enrolled. Conventional karyotyping was performed in all cases. CMA was performed as a reflex or complementary test when predefined clinical or cytogenetic criteria were present, including ultrasound abnormalities, high-risk screening/NIPT results, abnormal or uncertain karyotype findings, prior adverse pregnancy history suggestive of genetic etiology, parental chromosomal abnormalities, or patient request after counseling. Results Numerical chromosomal abnormalities were detected in 76/2200 cases (3.5%), and structural abnormalities were detected in 9/2200 cases (0.4%). The total abnormal cytogenetic yield was therefore 85/2200 cases (3.9%) when numerical and structural abnormalities were considered together. Age-stratified analysis showed an increasing trend in chromosomal abnormalities with advancing maternal age, reaching 10.4% in women aged > = 43 years. Cases with additional clinical indications showed higher abnormality rates than simple AMA. CMA was performed in selected cases and contributed to characterization of clinically relevant genomic abnormalities, supporting its role in indicated high-risk AMA pregnancies. Conclusion The Tamil Nadu cohort provides regional evidence on age-stratified cytogenetic risk in AMA pregnancies and supports the use of clearly defined criteria for integrating CMA with conventional karyotyping in prenatal diagnosis.